New mechanism of ion desorption from rare gas solids by multiply-charged ion impact. (July 2015) - Ban, Keisuke; Akiwa, Masaki; Sumita, Atsumi; Nidaira, Yuta; Kuwabara, Yuki; Tachibana, Takayuki; Hirayama, Takato
Synopsis: We have measured the absolute ion desorption yield from the surface of solid Ne and Ar by low-energy multiply-charged ion impact. Present results could not be explained by well-known Coulomb explosion model. We here propose a new mechanism of ion desorption.